ANALISIS PEMBERLAKUAN PSBB TERHADAP NILAI TUKAR RUPIAH DAN STOCK RETURN (Studi Kasus Pandemi Covid-19 Tahun 2020) - Rahmania Fitriani; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to analyze whether there are differences in the rupiah exchange rate and stock returns in the implementation of large-scale social restrictions (PSBB) during the 2020 Covid-19 pandemic. The sample in this study uses a purposive sampling technique. The research data obtained a sample of 194 manufacturing companies. The analytical method of this research is the Descriptive Statistical Test, Normality Test, and Hypothesis Testing. The results showed that there was a difference in the exchange rate before and after the implementation of the PSBB and there was a difference in stock returns before and after the implementation of the PSBB. Keywords : PSBB enforcement, Rupiah Exchange Rate, and Stock Return